The Geography of Inventiveness in the Primary Sector: Some Initial Results for New Zealand, 1880-1895 - Williams, R.; Oxley, Leslie (2016)
At the turn of the twentieth century, New Zealand was one of the wealthiest nations in the world on a per capita basis. We examine the role of innovation in explaining New Zealand's economic performance. Using a new dataset on patent applications for the period 1880-95, we consider whether the geographical concentration of innovative activity influenced economic activity. We find relationships between agricultural and pastoral output indices and inventiveness and between different regions and related industries. The results, however, are relatively weak. We conclude that tests of agglomeration effects in New Zealand during this period deserve further attention.